Mental health outcomes and their influencing factors on patients with COVID-19 in the Fangcang shelter hospital in China - Qingqing Xiao; Xia Huang; Lei Huang; Jingjun Wang; Yalin Huang; Yan Feng; Dan Wang; Ya Kou; Ya Wang (Journal of Infection in Developing Countries)
Introduction: Coronavirus disease 2019 (COVID-19) affects physical and mental health of patients. This study aimed to investigate the psychological distress, level of hope, and the role of families of patients with COVID-19 in the Fangcang shelter hospital (FSH) and explore potential influencing factors.